ALEJANDRO ROMUALDO: THE POET AS SEISMOGRAPHER. RHETORICAL ANALYSIS OF TWO POEMS FROM EDICIÓN EXTRAORDINARIA (1958) - Sánchez Flores, Miguel (2021)
This paper develops the analysis of two poems —“Al final y al cabo” and “Si me quitaran totalmente todo”— published in the book Edición Extraordinaria (1958) by the peruvian writer Alejandro Romualdo (1926-2008). This analysis will be developed from the main notions of General Textual Rhetoric, propose by authors such as Arduini (2000) and Bottiroli (1993). From the analysis, the limits of the tension between social and pure poetry, a category that has served as recurrent strategy to approach peruvian poetry of the 1950s. The text argues that rather than in the extreme points, Romualdo’s proposal is installed precisely in the mediation and that the collection of poems Edición extraordinaria, although it has a strong social them, also exposes the possibilities and limits of the aesthetic form.